A Zinc–Bromine Battery with Deep Eutectic Electrolytes. Issue 36 (30th October 2022) - Heo, Jiyun; Shin, Kyungjae; Kim, Hee‐Tak
Abstract: A deep eutectic solvent (DES) is an ionic liquid‐analog electrolyte, newly emerging due to its low cost, easy preparation, and tunable properties. Herein, a zinc–bromine battery (ZBB) with a Zn‐halide‐based DES electrolyte prepared by mixing ZnBr2, ZnCl2, and a bromine‐capturing agent is reported. The water‐free DES electrolyte allows a closed‐cell configuration for the ZBB owing to the prevention of Br2 evaporation and H2 evolution. It is found that the Cl − anion changes the structure of the zinc‐halide complex anions and demonstrated that it improves the ion mobility and electrode reaction kinetics. The DES electrolyte with the optimized ZnCl2 composition shows much higher rate capability and a cycle life 90 times longer than that of a ZnCl2 ‐free DES electrolyte. A pouch‐type flexible ZBB battery based on the DES electrolyte exhibits swelling‐free operation for more than 120 cycles and stable operation under a folding test, suggesting its potential in consumer applications such as wearable electronics. Abstract : Deep eutectic electrolytes are specifically designed for use in zinc–bromine batteries (ZBBs). By virtue of the water‐free property and superb Br2 adsorption ability of these electrolytes, problematic gas‐related issues are effectively suppressed, allowing the operation of ZBBs in consumer‐friendly configurations. The essential role of Cl − with regard to improving the performance capabilities of ZBBs has also been thoroughly studied.